2013
DOI: 10.1128/aac.01083-12
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of Drug Monitoring of β-Lactams in Obese Critically Ill Patients

Abstract: Severe sepsis and septic shock can alter the pharmacokinetics of broad-spectrum ␤-lactams (meropenem, ceftazidime/cefepime, and piperacillin-tazobactam), resulting in inappropriate serum concentrations. Obesity may further modify the pharmacokinetics of these agents. We reviewed our data on critically ill obese patients (body mass index of >30 kg/m 2 ) treated with a broadspectrum ␤-lactam in whom therapeutic drug monitoring was performed and compared the data to those obtained in critically nonobese patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
117
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(136 citation statements)
references
References 25 publications
15
117
2
1
Order By: Relevance
“…However, individual estimates in our study group ranged from 2.8 to 14.2 liters/h, which is not dissimilar to the range of other published data for critically ill or hospitalized patients (3 to 40 liters/h) (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Regarding piperacillin volume of distribution, the V c in this study was similar to other published data for both healthy volunteers and critically ill patients (13,18,19,21).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, individual estimates in our study group ranged from 2.8 to 14.2 liters/h, which is not dissimilar to the range of other published data for critically ill or hospitalized patients (3 to 40 liters/h) (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Regarding piperacillin volume of distribution, the V c in this study was similar to other published data for both healthy volunteers and critically ill patients (13,18,19,21).…”
Section: Discussionsupporting
confidence: 86%
“…We found that piperacillin pharmacokinetics in this population have high interindividual variability compared to those in healthy volunteers (12,13) but are similar to those in other critically ill or hospitalized patients (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Nonetheless, we have also found that renal function, i.e., CL CR , remains the most important determinant of piperacillin dosing requirements.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, prescribing physicians should always remember that diffusion of antibiotics in anatomical spaces cannot be easily predicted and is impossible to monitor. These patients are at risk of both under-and over-dosing, as recently reported in a study of serum b-lactam concentrations, where insufficient serum concentrations were observed in 32 % of cases and excessive concentrations in 25 % of cases [14]. In addition, some recent data suggest that in patients undergoing scheduled surgery, tissue distribution is altered, with a 30 % decreased penetration ratio compared to nonobese patients [15].…”
mentioning
confidence: 86%
“…However, recent studies suggest that higher targets are needed in critically ill patients to improve clinical outcome whilst minimizing the development of resistance. Concentrations four to fivefold greater than the MIC are associated with maximum bactericidal activity [3,4]. The PK/PD target was set at 100% fT > 4−5xMIC .…”
mentioning
confidence: 99%